2010
DOI: 10.1074/jbc.m110.142299
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptor α1 Subunit Mutation A322D Associated with Autosomal Dominant Juvenile Myoclonic Epilepsy Reduces the Expression and Alters the Composition of Wild Type GABAA Receptors

Abstract: A GABA A receptor (GABA A R) ␣1 subunit mutation, A322D (AD), causes an autosomal dominant form of juvenile myoclonic epilepsy (ADJME). Previous studies demonstrated that the mutation caused ␣1(AD) subunit misfolding and rapid degradation, reducing its total and surface expression substantially. Here, we determined the effects of the residual ␣1(AD) subunit expression on wild type GABA A R expression to determine whether the AD mutation conferred a dominant negative effect. We found that although the ␣1(AD) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 52 publications
2
38
0
1
Order By: Relevance
“…We replated the cells twice weekly. A description of plasmids expressing the ␣1, ␣3, ␤2, and ␥2 subunits was published previously (11). A plasmid expressing the ␤1 subunit was a generous gift from Dr. Robert Macdonald (Vanderbilt University).…”
Section: Methodsmentioning
confidence: 99%
“…We replated the cells twice weekly. A description of plasmids expressing the ␣1, ␣3, ␤2, and ␥2 subunits was published previously (11). A plasmid expressing the ␤1 subunit was a generous gift from Dr. Robert Macdonald (Vanderbilt University).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies demonstrated that the A322D mutation causes α1(A322D) protein misfolding with altered transmembrane topology (Gallagher et al, 2007) and rapid elimination by endoplasmic reticulum associated degradation (Bradley et al, 2008;Gallagher et al, 2007). This causes a 92% reduction of total α1(A322D) subunit expression (Ding et al, 2010). In addition, when expressed in vitro , the residual α1(A322D) subunit protein causes a small, but significant reduction of wild type GABA A R expression.…”
Section: Introductionmentioning
confidence: 99%
“…It must be also noted that a shortened lifetime caused by the epilepsy mutation A322D on ␣1-containing GABA A Rs has been proposed (74) (but also see Ref. 75). Interestingly, experiments on ␥2(R43Q) knock-in mice and transfected neurons or COS-7 cells have shown that ␣1 and ␣3 subunit surface expression was not reduced, despite a dramatic decrease in ␥2(R43Q) surface labeling (16,22).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%